Suicide rates amongst individuals from ethnic minority backgrounds: A systematic review and meta-analysis. (May 2022) - Troya, M.Isabela; Spittal, Matthew J.; Pendrous, Rosina; Crowley, Grace; Gorton, Hayley C; Russell, Kirsten; Byrne, Sadhbh; Musgrove, Rebecca; Hannam-Swain, Stephanie; Kapur, Navneet; Knipe, Duleeka
Summary: Background: Existing evidence suggests that some individuals from ethnic minority backgrounds are at increased risk of suicide compared to their majority ethnic counterparts, whereas others are at decreased risk. We aimed to estimate the absolute and relative risk of suicide in individuals from ethnic minority backgrounds globally. Methods: Databases (Medline, Embase, and PsycInfo) were searched for epidemiological studies between 01/01/2000 and 3/07/2020, which provided data on absolute and relative rates of suicide amongst ethnic minority groups. Studies reporting on clinical or specific populations were excluded. Pairs of reviewers independently screened titles, abstracts, and full texts. We used random effects meta-analysis to estimate overall, sex, location, migrant status, and ancestral origin, stratified pooled estimates for absolute and rate ratios. PROSPERO registration: CRD42020197940. Findings: A total of 128 studies were included with 6, 026, 103 suicide deaths in individuals from an ethnic minority background across 31 countries. Using data from 42 moderate-high quality studies, we estimated a pooled suicide rate of 12·1 per 100, 000 (95% CIs 8·4–17·6) in people from ethnic minority backgrounds with a broad range of estimates (1·2–139·7 per 100, 000). There was weak statistical evidence from 51 moderate-high quality studies that individuals from ethnic minority groups were more likely to die by suicide (RR 1·3 95% CIs 0·9–1·7) with again a broad range amongst studies (RR 0·2–18·5). In our sub-group analysis we only found evidence of elevated risk for indigenous populations (RR: 2·8 95% CIs 1·9–4·0; pooled rate: 23·2 per 100, 000 95% CIs 14·7–36·6). There was very substantial heterogeneity ( I 2 > 98%) between studies for all pooled estimates. Interpretation: The homogeneous grouping of individuals from ethnic minority backgrounds is inappropriate. To support suicide prevention in marginalised groups, further exploration of important contextual differences in risk is required. It is possible that some ethnic minority groups (for example those from indigenous backgrounds) have higher rates of suicide than majority populations. Funding: No specific funding was provided to conduct this research. DK is funded by Wellcome Trust and Elizabeth Blackwell Institute Bristol. Matthew Spittal is a recipient of an Australian Research Council Future Fellowship (project number FT180100075) funded by the Australian Government. Rebecca Musgrove is funded by the NIHR Greater Manchester Patient Safety Translational Research Centre (PSTRC-2016-003).